(1+1⼀2+1⼀3+1⼀4)乘(1⼀2+1⼀3+1⼀4+1⼀5)-(1+1⼀2+1⼀3+1⼀4+1⼀5)乘(1⼀2+1⼀3+1⼀4)

2025-02-24 00:42:50
推荐回答(5个)
回答1:

上面的错了,应该是:
令(1+1/2+1/3+1/4)=a,(1/2+1/3+1/4+1/5)=b
原式=ab-(a+1/5)*(b-1/5)
=ab-(ab+1/5b-1/5a-1/25)
=ab-ab-1/5b+1/5a+1/25
=1/5(a+b)+1/25
=1/5*4/5+1/25
=4/25+1/25
=1/5

回答2:

解:原式=1*(1/2+1/3+1/4+1/5)+(1/2+1/3+1/4)*(1/2+1/3+1/4)-1*(1/2+1/3+1/4)-(1/2+1/3+1/4+1/5)*(1/2+1/3+1/4)
=1/2+1/3+4/4+1/5-1/2-1/3-1/4
=1/5
本座是你班长

回答3:

(1+1/2+1/3+1/4)*(1/2+1/3+1/4+1/5)-(1+1/2+1/3+1/4+1/5)*(1/2+1/3+1/4)
=1*(1/2+1/3+1/4+1/5)+(1/2+1/3+1/4)*(1/2+1/3+1/4+1/5)-1*(1/2+1/3+1/4)-(1/2+1/3+1/4+1/5)*(1/2+1/3+1/4)
=(1/2+1/3+1/4+1/5)-(1/2+1/3+1/4)
=1/5

回答4:

(1+1/2+1/3+1/4)*(1/2+1/3+1/4+1/5)-(1+1/2+1/3+1/4+1/5)*(1/2+1/3+1/4)
=(1+1/2+1/3+1/4)*(1/2+1/3+1/4)+1/5*(1+1/2+1/3+1/4)-(1+1/2+1/3+1/4)*(1/2+1/3+1/4) -1/5*(1/2+1/3+1/4)
=1/5
-----------------------------
(1+1/2+1/3+1/4)=a,(1/2+1/3+1/4)=b

(1+1/2+1/3+1/4)乘(1/2+1/3+1/4+1/5)-(1+1/2+1/3+1/4+1/5)乘(1/2+1/3+1/4)
=a*(b+1/5)-(a+1/5)*b
=ab+a/5-ab-b/5
=(a-b)/5
=1/5

回答5:

(1+1/2+1/3+1/4)乘(1/2+1/3+1/4+1/5)=(1/2+1/3+1/4)乘(1/2+1/3+1/4+1/5)+(1/2+1/3+1/4+1/5)
(1+1/2+1/3+1/4+1/5)乘(1/2+1/3+1/4)=(1/2+1/3+1/4+1/5)乘(1/2+1/3+1/4)+(1/2+1/3+1/4)
原式=(1/2+1/3+1/4)乘(1/2+1/3+1/4+1/5)+(1/2+1/3+1/4+1/5)-1/2+1/3+1/4+1/5)乘(1/2+1/3+1/4)-(1/2+1/3+1/4)=(1/2+1/3+1/4+1/5)-(1/2+1/3+1/4)
=1/5